Global experience with the nellix endosystem for ruptured and symptomatic abdominal aortic aneurysms: $hMichel M. P. J. Reijnen, Jorg L. de Bruin, Elke G. E. Mathijssen, Eric Zimmermann, Andrew Holden, Paul Hayes, Dainis Krievins, Dittmar Böckler, Jean-Paul P. M. de Vries, Matt M. Thompson - Reijnen, Michel; Bruin, Jorg L. de; Mathijssen, Elke G. E.; Zimmermann, Eric; Holden, Andrew; Hayes, Paul; Krievins, Dainis; Böckler, Dittmar; Vries, Jean-Paul P. M. de; Thompson, Matt M. (Journal of endovascular therapy, 2016)
Purpose: To assess the feasibility and safety of the endovascular aneurysm sealing (EVAS) technique in the treatment of acute abdominal aortic aneurysm (AAA). M...